The Body Divine: The Symbol of the Body in the works of Teilhard de Chardin and Ramanuja - Vineeth, V F (Journal of Dharma, 1992)
Anne Hunt Overzee, The Body Divine — The Symbol of the Body in the works of Tei/hard de Chardin and Ramanuja. Cambridge : Cambridge University press, 1992, pp. xv + 218, 49.95.